Olive Fruit Fly, Bactrocera oleae (Rossi) (Insecta: Diptera: Tephritidae) - Howard V. Weems; James L. Nation (EDIS)
Revised! EENY-113, a 4-page illustrated fact sheet by H. V. Weems and J. L. Nation, is part of the Featured Creatures collection. It describes this serious pest of olives in the Mediterranean — distribution, identification, life history and habits, hosts, and management procedures. Includes references. Published by the UF Department of Entomology and Nematology, July 2009.